2014
DOI: 10.1111/are.12625
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of alternative proteins to the growth of Juvenile Cobia, Rachycentron canadum (Linnaeus)

Abstract: Five isonitrogenous and isocaloric diets were fed to juvenile cobia, to assess the relative contribution of different proteins (fish meal, soybean meal, corn gluten and beer yeast) to the growth of cobia. The dietary effects on nitrogen and carbon turnover and on the isotopic diet-consumer discrimination factors (D 15 N and D 13 C) were also assessed. Growth results showed that the final body weight, growth rate, feed conversion ratio and protein efficiency ratio of cobia fed diets with alternative protein wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…(2016). Previous studies have shown that cobia ( Rachycentron canadum ; Zhou et al., 2016) and brown‐marbled grouper ( Epinephelus fuscoguttatus ; Chen, Zhou, & Gu, 2013) reached the highest growth rates when fed with diets containing FM as the only protein source. Such contrasting observations might be explained by the fact that Nile tilapia is an omnivore, while cobia and grouper are carnivores and have different dietary amino acids requirements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016). Previous studies have shown that cobia ( Rachycentron canadum ; Zhou et al., 2016) and brown‐marbled grouper ( Epinephelus fuscoguttatus ; Chen, Zhou, & Gu, 2013) reached the highest growth rates when fed with diets containing FM as the only protein source. Such contrasting observations might be explained by the fact that Nile tilapia is an omnivore, while cobia and grouper are carnivores and have different dietary amino acids requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to calculate the contribution of a specific protein source to animal growth with a stable isotope mixing model, the time required for consumers to reach isotopic equilibrium with their diet should be considered and estimated by a diet shift experiment when possible. Many diet shift experiments have been conducted to estimate isotopic half‐life and diet‐tissue isotopic equilibrium values with observed data for a diverse range of animal taxa and tissue types (Buchheister & Latour, 2010; Gamboa‐Delgado & Le Vay, 2009; Seminoff, Bjorndal, & Bolten, 2007; Suzuki, Kasai, Nakayama, & Tanaka, 2005; Zhou et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Após o sucesso da criação em Taiwan, a produção de beijupirás começou a se expandir para as demais partes do mundo. Existem relatos de criação e iniciativas de pesquisa na China (ZHOU et al, 2016), Vietnã (HUY et al, 2006), Taiwan (LIAO et al, 2004, Estados Unidos (WEIRICH et al, 2004;RICHE et al, 2013), Porto Rico, Belize, Ilhas Reunião (GAUMET et al, 2007, Japão (NAKAMURA, 2007), Indonésia (WAHJUDI;MICHEL, 2007), México, Tailândia, Irã, República Dominicana, Bahamas, Martinica, Panamá, Austrália, Ilhas Marshall (BENETTI et al, 2008) e Índia (GOPAKUMAR et al, 2012PHILIPOSE et al, 2013). Trabalhos mais recentes, como os de Benetti et al Houve um crescimento na produção desta espécie nos últimos anos: em 2000, eram produzidas 2,6 mil toneladas sendo o Taiwan o único produtor com dados de produção; em 2003, a China também passou a ter uma produção significativa com o total produzido aumentando para 18,6 mil toneladas e, desde então, ela é o maior produtor da espécie; em 2008, o Vietnã também passou a apresentar uma grande produção e a produção mundial era de 26,5 mil toneladas; em 2012, a produção era de 40,1 mil toneladas e, em 2014, de 40,3 mil toneladas (FAO, 2011(FAO, -2016.…”
Section: Parte I: Avaliação Do Estado Fisiológico De Juvenis De Beijuunclassified
“…Os maiores problemas encontrados ao longo dos anos de criação se referem principalmente à alimentação, patógenos e necessidade de mais pesquisas para um melhor conhecimento da espécie. Em alguns países, como China, Taiwan e Vietnã, ainda se utilizam restos de peixe e espécies de pequeno tamanho sem valor comercial como alimentação das criações de beijupirás, porém a oferta destes peixes é limitada (TIEN et al, 2016;ZHOU et al, 2016). O desenvolvimento da formulação de rações também está atrasado se comparado com a de outros peixes marinhos que são criados em larga escala, como salmão, e, apesar dos diversos estudos que estão sendo realizados, ainda não se sabe, com maior profundidade, as exigências nutricionais da espécie (TIEN et al, 2016).…”
Section: Parte I: Avaliação Do Estado Fisiológico De Juvenis De Beijuunclassified